Brain Tumour Detection and Grading Using Raman Scattering: Analogy from Semiconductors for Solving Biological Problem. Issue 1 (2nd January 2022) - Kaushik, Ritika; Rani, Chanchal; Neeshu, Km; Tanwar, Manushree; Pathak, Devesh K.; Chaudhary, Anjali; Siraj, Fouzia; Jha, Hem C.; Kumar, Rajesh
ABSTRACT: Subtle changes in Raman spectral line shape have been observed from malignant human brain cells and its possibility for being used in detection and grading of Glioma has been explored here. The latter has been developed as a result of the fact that the width of the Raman spectra is more sensitive, as compared to the peak position, to the brain tumours. The perturbations induced by the cell modification, as a consequence of the cancerous growth, may be responsible for the width's variation in the Raman spectrum due to vibrational lifetime alteration enforced at the molecular levels. A consistent cancer-induced effect on the spectral width has been observed for three different brain cells' Raman modes. Raman spectral analysis reveals that for cancerous cells, the FWHM varies up to 35% in comparison with the healthy cells. It has been established how a careful analysis of Raman spectra can help in easy detection of brain tumours. The methodology has been appropriately validated. The proposed model for malignancy detection is based on analogous behaviour of Raman spectral width variation in biological samples with semiconductor nanoparticles. Graphical abstract: